Why Do Achievement Measures Underpredict Female Academic Performance?. Issue 1 (25th January 2017) - Mattern, Krista; Sanchez, Edgar; Ndum, Edwin
Abstract : In the context of college admissions, the current study examined whether differential prediction of first‐year grade point average (FYGPA) by gender could be explained by an omitted variable problem—namely, academic discipline, or the amount of effort a student puts into schoolwork and the degree to which a student sees him/herself as hardworking and conscientious. Based on nearly 10, 000 college students, the current study found that differences in intercepts by gender were reduced by 45% with the inclusion of academic discipline in a model that already included high school grade point average (HSGPA) and ACT Composite score. Moreover, academic discipline resulted in an additional 4% of variance accounted for in FYGPA. Gender differences in slopes were not statistically significant ( p > .001) regardless if academic discipline was included in the model. The findings highlight the utility of taking a more holistic approach when making college admission decisions. Namely, the inclusion of noncognitive measures has benefits that are twofold: increased predictive validity and reduced differential prediction.